2017
DOI: 10.1039/c7ra03365f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a poly(amidoxime-hydroxamic acid) cellulose derivative and its application in heavy metal ion removal

Abstract: Amidoxime and hydroxamic acid functional groups have comparable chelating ability with synthetic resins, but the synthesis of cellulose fibers bearing amidoxime and hydroxamic acid functional groups using simple and effective strategies have yet to be developed. In this study, a poly(amidoxime-hydroxamic acid) cellulose derivative (pAHA-cellulose) was prepared via free radical polymerization followed by an oximation reaction. A series of microscopic analyses and spectral tests proved that the pAHA-cellulose wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The peaks at 44 ppm ( b ) and 42 ppm ( b’ ) correspond to the CH of acrylamide and acrylic acid. Due to the low charge density of Zetag 4100 and Zetag 4110 (<10% and ~25% acrylic acid, respectively) and the high charge density of WAS590 (~50% acrylic acid), the intensity of peak at 182 ppm is relatively strong for WAS590 and weak for Zetag 4100 and Zetag 4110 23,24 . In the modified polymers (Figure 2, WAS590‐HA, Zetag4100‐HA, and Zetag4110‐HA), the new peaks at 172‐173 ppm ( e ) and 38 ppm are observed, which confirm the presence of a (C=O)NHOH and CH‐(C=O)NHOH of the PHA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks at 44 ppm ( b ) and 42 ppm ( b’ ) correspond to the CH of acrylamide and acrylic acid. Due to the low charge density of Zetag 4100 and Zetag 4110 (<10% and ~25% acrylic acid, respectively) and the high charge density of WAS590 (~50% acrylic acid), the intensity of peak at 182 ppm is relatively strong for WAS590 and weak for Zetag 4100 and Zetag 4110 23,24 . In the modified polymers (Figure 2, WAS590‐HA, Zetag4100‐HA, and Zetag4110‐HA), the new peaks at 172‐173 ppm ( e ) and 38 ppm are observed, which confirm the presence of a (C=O)NHOH and CH‐(C=O)NHOH of the PHA.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxamic acid containing polymers are well known for their chelation and complexation with metal ions, especially Fe 3+ and Cu 2+ 24,25 . Table 2 illustrates the physicochemical characteristics of the SW and PW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD diffraction maxima are recorded at 2θ values of around 15°, 16°, 22°, and 34°. These peaks are characteristic of the cellulose and can be attributed to the crystalline planes (hkl) (101), (10-1), (002), and (040), respectively, attributed to cellulose I crystal structure [20,27,28]. Furthermore, the crystallinity index (CrI) was calculated using Equation 1, resulting in a 75% for CRS.…”
Section: Desorption Experimentsmentioning
confidence: 99%
“…Haron et al [15] removed Cu (II) ions using hydroxamic acid functionalized PMMA-g-oil palm empty fruit bunch. Jiao et al [16] removed Cu 2+ , Zn 2+ , Pb 2+ , and Cr 3+ using a new poly(amidoximehydroxamic acid) cellulose derivative obtained by grafting of ethyl (ethoxymethylene) Cyanoacetate onto cellulose followed by reaction with Hydroxyl amine hydrochloride. Rahman et al reported a lot of work in this direction [17][18][19] using cellulose from different sources grafted by poly(methyl acrylate) and treated with Hydroxyl amine hydrochloride to remove different metals including Cu 2+ , Fe 3+ , Mn 2+ , Co 3+ , Cr 3+ , Ni 2+ , and Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%